(untitled) (Research, Society and Development, 2020)
Sialolithiasis is one of the most common diseases of the salivary glands. Sialoliths usually occur in the submandibular ducts or gland and are classified as being of unusual size or “giant” sialoliths if any dimension exceeds 15 mm. The aim of this work is to report a clinical case of sialolith located in the submandibular gland, as well as to discuss the pertinent literature on the subject. A 68-year-old female patient attended the CTBMF service at the Trauma Hospital of Campina Grande, complaining of discomfort and episodes of pain, redness in the left submandibular region and dry mouth. A calcified mass measuring 16 x 10 mm was evidenced by computed tomography, in the path of the duct of the left submandibular gland. Salivary calculus excision was performed under general anesthesia. After accessing and removing it, a jelco nº 16 was installed to help re-epilate the site in order to maintain the patency of the involved duct. Therefore, the correct evaluation, considering the location and size of the sialolith, is indispensable for the treatment plan and the good execution, in this case, the surgical excision of the sialolite was the technique considered and positive results were obtained.